Endoplasmic Reticulum Stress Signaling Is Involved in Mitomycin C(MMC)-Induced Apoptosis in Human Fibroblasts via PERK Pathway - Shi, Kun (Public Library of Science, 2013)
Endoplasmic reticulum (ER) stress-mediated cell apoptosis has been implicated in various cell types, including fibroblasts. Previous studies have shown that mitomycin C (MMC)-induced apoptosis occurs in fibroblasts, but the effects of MMC on ER stress-mediated apoptosis in fibroblasts have not been examined. Here, MMC-induced apoptosis in human primary fibroblasts was investigated by exposing cells to a single dose of MMC for 5 minutes. Significant inhibition of cell proliferation and increased apoptosis were observed using a cell viability assay, Annexin V/propidium iodide double staining, cell cycle analysis, and TUNEL (terminal deoxynucleotidyl transferase dUTP nick-end labeling) staining. Upregulation of proapoptotic factors, including cleaved caspase-3 and poly ADP-ribose polymerase (PARP), was detected by Western blotting. MMC-induced apoptosis was correlated with elevation of 78-kDa glucose-regulated protein (GRP78) and C/EBP homologous protein (CHOP), which are hallmarks of ER stress. Three unfolded protein response (UPR) sensors (inositol-requiring enzyme 1, IRE1; activating transcription factor 6, ATF6; and PKR-like ER kinase, PERK) and their downstream signaling pathways were also activated. Knockdown of CHOP attenuated MMC-induced apoptosis by increasing the ratio of BCL-2/BAX and decreasing BIM expression, suggesting that ER stress is involved in MMC-induced fibroblast apoptosis. Interestingly, knockdown of PERK significantly decreased ER stress-mediated apoptosis by reducing the expression of CHOP, BIM and cleaved caspase-3. Reactive oxygen species (ROS) scavenging also decreased the expression of GRP78, phospho-PERK, CHOP, and BIM. These results demonstrate that MMC-induced apoptosis is triggered by ROS generation and PERK activation.